Online or Offline Learning: Systematic Literature Review Analysis In Indonesia - Thoyib Bakhtiar Zaini; Dendi Yuda Safrullah; Kinanti Pangestu; Rudiana Rudiana; Muh. Syaiful Saehu (STAI Hubbulwathan Duri, 2023)
Online or offline learning has an impact on students who are continuing their education. The purpose of this study was to look at the learning process conducted online and the impact it had. The research uses a systematic literature review method. The data collection analyzed includes 15 publication documents. Data were obtained through a database of dimensions in 2019–2023. In data collection, limitations are made, and then the analysis step uses the NVivo software to obtain a more accurate theme point. Results obtained through in vivo analysis include brain capabilities for strategically and effectively understanding visual priming, most notably requiring tissue to access everything. Teaching ethics in business can thus develop learning systems management, be able to detect cheating activities, integrate culture-based character education, promote high-level thinking skills, and provide new energy. Meanwhile, the impact of moving from offline to online is hybrid learning, shifting learning methods, creative problem-solving-flipped classroom vocational education, and transition.